Subject and Hero in the Latin American Historical Novel (An Approach to Lukacs' Theory). (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
Dialectics presupposes a lack of end, term, effect, or absolute; its metaphor is a continuous dynamo, almost pure transit except for the historical inflection, its fact, objectification, concreteness, and praxis. So, where does it lead? The lights of the utopian city should guide us, but they are diffuse and mistaken; the Southern Cross should lead pilgrims to the revolutionized world, but the paths bifurcate into empty labyrinths. History is indifferent to the compass, the guide, the sign, the mark, the index. History does not teach how to make history, but Lukacs meticulously teaches the dialectical process between the subject and the hero, between history and literature. He teaches the crystallizations or condensations of historical meanings.